Kajian tentang Perwujudan Nilai Juang pada Tari Turak (Studi Kasus Kecamatan Suku Tengah Lakitan (STL) Ulu Terawas Kabupaten Musi Rawas Sumatera Selatan) - Ira Miyarni Sustianingsih; Risa Marta Yati (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2018)
Turak Dance is a traditional dance belonged to the community in the Central District of Lakitan (STL) Ulu Terawas Musi Rawas Regency of South Sumatra. Now adays, the existence of Turak Dance is less known to the public in the region of Musi Rawas Regency, both in the terms of performances and the values contained in this dance. The research design was qualitative research with ethnography approach. This research procedure includes three stages: (1) preparation field stage; (2) research field stage, including: data collection techniques, determining subject and object of research, and clarification of data; and (3) data analysis and reporting of research. Based on the results of this research it was known that this dance was created in the history time of the people in Tanjung Sakti (now changes into the Central Tribe Lakitan (STL) Ulu Terawas the arrival of Dutch entourage guests and envoys from the Kingdom of Palembang who intended to control the territory of Tanjung Sakti. Turak Dance at this moment began to be introduced to the community in the region of Musi Rawas Regency and surrounding areas. However, many of the fighting values that exist in this dance less informed to the wider community, because only a few prominent leaders who know the history of the emergence of this Turak Dance. Conclusions of the past Turak Dance is a dance to fight the Dutch invaders. But now Turak Dance is used to entertain guests and traditional ceremonial events to find out the value contained in Turak Dance. Keywords: Juang Value, Turak Dance